Risk and protective factors for sudden infant death syndrome - Aghata Marina de Faria Oliveira; Paula Rosenberg de Andrade; Eliana Moreira Pinheiro; Ariane Ferreira Machado Avelar; Priscila Costa; Aline Santa Cruz Belela-Anacleto (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: To verify the occurrence of the risk and protective factors for sudden infant death syndrome during nursing consultation. Methods: Retrospective cohort study conducted based on medical records from a primary care unit in the municipality of São Paulo. The sample consisted of 63 infants assisted from January to December 2016. Results: The average age of infants was 3.2 months. The main risk factors identified were the presence of soft objects in the crib (93.6%) and bed sharing (58.7%). Predominant protective factors were breastfeeding (95.2%) followed by updated immunization (90.5%). Conclusions: Risk and protective factors for sudden infant death syndrome were identified in the study sample, indicating the importance of addressing the issue with families of children under 1 year of age to prevent the occurrence of such events.